Self-attenuation in gamma-ray spectrometry: theory, correction methods, and applications - Almaz, Ekrem; Landsberger, Sheldon (Elsevier Sci Ltd, 2026)
High-resolution gamma-ray spectrometry is widely used to quantify radionuclides in environmental, geological, and industrial samples. However, its accuracy is often compromised by self-attenuation-the absorption or scattering of gamma photons within the sample matrix-leading to significant underestimation of activity if uncorrected. This review provides a comprehensive synopsis of self-attenuation effects, correction methods, and practical applications. We begin by explaining the physics of gamma-ray attenuation and defining the linear attenuation coefficient, which underpins self-attenuation effects. We then examine analytical and semi-analytical models for self-attenuation correction-from classical formulations of attenuation factors to more recent compact analytical expressions and discuss their assumptions and applicable sample geometries. Empirical approaches are reviewed next, including transmission measurements through the sample and the use of matrix-matched calibration standards, along with validation studies using reference materials and real-world samples. We also highlight the powerful role of Monte Carlo simulations and other numerical methods for handling complex, heterogeneous samples that are intractable analytically. The dependence of selfattenuation on sample parameters-such as density, elemental composition, geometry, and photon energy-is emphasized, showing why simple one-size-fits-all corrections fail for many real samples. We illustrate the practical significance of self-attenuation corrections through examples across diverse fields: environmental radioactivity monitoring (e.g. soil and sediment assays), the nuclear industry (e.g. waste drum measurements), neutron activation analysis, and material science. Notably, we incorporate a benchmark case study of a zinc-rich industrial composite matrix to demonstrate the challenges in heavy-metal samples. Finally, we present a comparative analysis of analytical, empirical, and Monte Carlo-based correction methods, outlining their relative advantages, limitations, and typical uncertainties. All sections include key equations, figures, and summary tables. This review is intended as a detailed reference for researchers and professionals seeking to understand and mitigate self-attenuation effects in gamma-ray spectrometric measurements, especially those in environmental radioactivity studies.
Keywords: Absorption Corrections; Efficiency Calibration; Environmental-Samples; Hpge Detector; Transmission Method; Cylindrical Sources; Sediment Samples; Pb-210; Well; Energy